EPV 22. Functional connectivity of the pMFC and its relation to akinesia in Parkinson's disease. Issue 9 (September 2016) - Hensel, L.; Hoffstaedter, F.; Caspers, J.; Mathys, C.; Michely, J.; Heller, J.; Eickhoff, C.R.; Reetz, K.; Südmeyer, M.; Fink, G.R.; Schnitzler, A.; Grefkes, C.; et al.
Abstract : Introduction: One of the key symptoms of Parkinson's disease (PD) is the impairment of spontaneous movement also known as akinesia (Berardelli et al., 2001 ). Correspondingly, patients performing motor tasks feature abnormal activation in regions such as posterior medial frontal cortex (pMFC) and putamen (Herz et al., 2013 ). These areas play crucial roles in the internal timing of volitional movements in healthy individuals (Hoffstaedter et al., 2013 ). Yet, little is known about these regions' functional connectivity (FC) in PD and its relationship with akinesia. The present study investigated FC alterations of the 'motor initiation network' in PD, using a seed-based resting-state (RS) analysis. Methods: RS fMRI data of 60 patients diagnosed with idiopathic PD (mean age 61.6 ± 10.2; mean disease duration 6.5 ± 5.5 years) and 72 healthy volunteers (mean age 60.1 ± 8.8, matched for age, gender and within-scanner movement) was acquired at two sites. After spatial preprocessing (realignment, normalization, smoothing), temporal filtering was conducted including motion confound removal and band-pass filtering. Seeds in bilateral putamen and pMFC were derived from a meta-analysis on volitional movements (Hoffstaedter et al., 2014 ). Two more seeds were selected in bilateral primary motor cortex (M1). For each seed, (i) whole-brain FC and (ii) its interaction with akinesia (UPDRS item 3.14) were assessed. RS networks for the aforementioned regions were first mapped in healthy controls only: Contrasting each region's FC to the FC of all respective other seeds yielded maps of specific connectivity with either seed. These networks were then used to map whole-brain corrected changes of FC in PD. Results were cluster-level corrected for multiple comparisons ( p  < 0.05). Results: In healthy participants, RS analysis differentiated three networks, specifically (more than all other seeds) connected to bilateral putamen, bilateral M1, and pMFC. In PD, all seeds consistently featured decreased FC with regions in their most related network. That is, M1 mainly showed FC decrease within the M1-related network, pMFC lost FC with anterior insulae and left dorsolateral prefrontal cortex (DLPFC; pMFC-related network), and putamen lost FC with caudate nucleus, pallidum and thalamus (Putamen-related network). Additionally, putamen FC decreased extensively also in those regions more related to M1 and pMFC, including visual, superior parietal, primary somatosensory, M1, pMFC and DLPFC. Testing for each seed's interaction with akinesia, pMFC showed a decreased FC with inferior parietal lobe (IPL) in the pMFC-related network. In turn, FC of the other seeds did not significantly relate to akinesia. Conclusions: The present study examined RS FC changes of bilateral putamen, M1 and pMFC in PD. In patients, putamen FC suggests a marked cortico-striatal decoupling, in line with pathophysiological models of the disease (Braak et al., 2004 ). In contrast, pMFC featured more selective FC decreases, predominantly in regions involved in motor control (Hoffstaedter et al., 2013; Hoffstaedter et al., 2014 ). Notably, akinesia was exclusively related to pMFC-connectivity. With increasing impairment, pMFC decoupled from the right IPL. In sum, the present study demonstrates a disruption of cortico-striatal FC and specifies the role of pMFC - IPL connectivity for movement initiation in PD.